DOI: 10.31274/rtd-180813-7046
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration and plant growth across a chronosequence of tallgrass prairie reconstructions

Abstract: An understanding of changes in soil respiration (R s) and plant growth in tallgrass prairies planted into formerly cultivated land is critical if we are to predict the effects of grassland reconstructions on belowground carbon cycling. In addition, predicting changes in the ecosystem carbon balance in grassland reconstructions will require identifying the climatic and biological controls on R s across a landscape of cultivated and reconstructed grassland ecosystems. This study used a 12 yr chronosequence of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Forest soils are a major sink of terrestrial carbon containing more than double the amount of carbon found in forest tree biomass [1,2] and play a fundamental role in the global carbon cycle [3][4][5][6]. e role of forest soils as either a source or sink has become vital when assessing changes in atmospheric carbon dioxide concentrations mainly due to the growing interest of reducing the greenhouse emissions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Forest soils are a major sink of terrestrial carbon containing more than double the amount of carbon found in forest tree biomass [1,2] and play a fundamental role in the global carbon cycle [3][4][5][6]. e role of forest soils as either a source or sink has become vital when assessing changes in atmospheric carbon dioxide concentrations mainly due to the growing interest of reducing the greenhouse emissions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%